Synthesis and characterization of superconducting magnesium diboride (MgB2) nanomaterials through horizontal vapor phase crystal growth technique - Embalzado, Renante C. (Animo Repository, 2010)
Superconducting Magnesium Diboride (MgB2) nanomaterials were synthesized using Horizontal Vapor Phase Crystal Growth (HVPCG) technique. In this method, thirty-five milligrams (35mg) of MgB2 powder obtained from Accumet Material Co was measured and loaded into a quartz tube with one end sealed. The tube was then connected to a Thermionics High-Vacuum System and sealed it with a pressure of approximately 10 -6 Torr using a mixture of LPG and oxygen gas. The tube was then placed inside the Thermolyne Tube Furnace which was oriented horizontally. The sample was then fired at the temperatures of 900℃, 1000℃, 1100℃ and 1200℃ respectively with heating time of 2 – 12 hours with a two- hour increment. The grown structures were collected from the quartz tube and investigated involving the characterization of surface morphology, crystal structure and critical temperature. Electronic resistivity of the grown nanomaterials was investigated using Hall Effect Measurement System in a closed-cycle helium cooled cryopump. Resistance of the synthesized materials was measured using standard four-point probe method and resistance vs. temperature (ρ-T) curve was plotted using IEEE software. The result revealed that the critical temperature of MgB2 nanomaterials fabricated at 1 000°C is 33K, which is close to the Tc of its bulk counterpart which is 34K. The extrapolated offset temperature is 13K and the transition to superconducting state is very broad with a width ΔT= 20 K. The broadened transition interval is indicative of low connectivity and a large amount of defects and impurities in the sample. The low Tc of the fabricated nanomaterial is the effect of the increase grain boundaries of the nanomaterials that resulted to less connectivity and more resistance. The result shows that the critical temperature is dependent on the grain size of the sample. By decreasing the crystal size of the MgB2 to nanoscale, the critical temperature has dropped by 1K. Surface Morphology of the grown materials was investigated using JEOL JSM-5310 scanning electron microscope. SEM images revealed nanomaterials of different structures such as nanowires, nanobelts, nanorods and nanoparticles. The orientation of the grown nanostructures was random in direction on all samples. MgB2 synthesized at higher temperatures with longer heating time produced more nanomaterials. A number of nanomaterials, particularly nanowires, formed on the colder part of the tube. Optimum growth parameters are 1200°C and 12 hours. Crystal structure of synthesized materials was studied using X-ray Diffractometer Spectroscopy. X-ray diffraction patterns were collected with Cu Kα radiation (λ=0.154178nm) over a 2θ range from 10° to 80° at a step width of 0.02°. The results revealed that the nanomaterials have growth orientation of (100), (101), and (110), which indicated that the synthesized structures are polycrystalline. This finding is consistent with the result of the SEM images. Careful analysis showed that the synthesized material has a hexagonal crystal structures with lattice parameters of a and c – axes of 3.085 Å and 3.524 Å, respectively, which is identical to the bulk sample